4-Formylphenyl boronic acid grafted amino MCM-41 for efficient adsorption of Cu(II) ions in aqueous medium: isotherm, kinetic and optimization studies. (3rd April 2022) - Kaur, Inderpreet; Kaur, Navjot; Singh, Bhupinder Pal; Kumar, Rajeev; Chawla, Jyoti
Abstract: A novel adsorbent, 4-formylphenyl boronic acid grafted amino MCM-41 (b-MCM) was synthesized and characterized followed by its application for the removal of copper(II) ions from water. Adsorption data was subjected to isotherm and kinetic studies. Maximum adsorption capacity calculated from Langmuir isotherm was found to be 215.40 mg/g. Adsorption process was optimized using response surface methodology (RSM) for achieving the maximum efficiency at different pH, temperature and concentration. b-MCM was also successfully applied as packing material in column studies and found to remove 100% of Cu(II) ions which proves its candidature as an excellent alternative for wastewater treatment.